Cytogenetic study in seven species of Zingiberaceae family from Bueng Kan Province, Thailand - PIYAPORN SAENSOUK; SURAPON SAENSOUK; TANANSUK PHECHPHAKDEE; AREERAT RAGSASILP (Society for Indonesian Biodiversity, 2023)
Abstract. Saensouk P, Saensouk S, Phechphakdee T, Ragsasilp A. 2022. Cytogenetic study in seven species of Zingiberaceae family from Bueng Kan Province, Thailand. Biodiversitas 24: 68-77. Bueng Kan province is located in the Northeast Thailand. The family Zingiberaceae in Bueng Kan Province was found to be a highly diverse plant. The aim of this study was to study the chromosome numbers, fundamental number (NF), karyotype form and ideogram analysis of seven species in the family Zingiberaceae from Bueng Kan province, Northeast Thailand. The seven species of Zingiberaceae family-namely Boesenbergia rotunda (L.) Mansf., Curcuma aeruginosa Roxb., Etlingera elatior (Jack) R.M.Sm., Kaempferia elegans Wall., Kaempferia pulchra Ridl., Kaempferia rotunda L. and Zingiber montanum (J.Koenig) Link ex A.Dietr. in this study have been recognized the cytogenetic study including the chromosome number from root tips, karyology, NF, symmetrical karyotype, RL, CI, and ideogram. The chromosome numbers of all species were reported between 2n = 20 and 68. The NF of six species was reported for the first time. The symmetrical karyotype formula has been recognized as a symmetrical karyotype (four species) and an asymmetrical karyotype (three species). The karyotype formula of five species was reported for the first time. The ideogram of all species was provided for the first time. The cytogenetic data of all species in this study can be used for identification.